Smoking intensity and bladder cancer aggressiveness at diagnosis - Barbosa, André L. A. (PLoS One, 2018)
OBJECTIVE: To explore the relation between cigarette smoking intensity and bladder cancer aggressiveness at first diagnosis. METHODS: Patients diagnosed with urinary bladder cancer (BC) between 1995–2011 under the age of 75 years were retrospectively identified from the Netherlands Cancer Registry and invited for a study on genetic and lifestyle risk factors for BC. Information on patients’ self-reported smoking history was retrieved by means of a postal questionnaire. Tumors were stratified regarding the risk of progression defined by tumor stage and grade. Multinomial logistic regression was used to analyze the relation between smoking intensity and aggressiveness of the tumor. RESULTS: The UBC study population comprised 323 (17.4%) never smokers, 870 (46.8%) former cigarette smokers, and 630 (33.9%) current cigarette smokers. A higher smoking amount was a risk factor of getting high-risk non-muscle invasive bladder cancer (NMIBC) compared with low-risk NMIBC in ever and former cigarette smokers (OR: 1.02 per cigarette smoked, 95% CI: 1.00–1.03 and OR: 1.03, 95% CI: 1.01–1.05, respectively). A statistically significant dose-response increase in the risk of a more aggressive cancer type (high-risk NMIBC and MIBC) was observed with increasing smoking duration among former smokers (p for trend 0.035 and 0.008, respectively). No significant association of the evaluated smoking intensity variables was observed in current smokers. A longer time of smoking cessation correlated with a lower odds of a more aggressive cancer. CONCLUSION: We observed a weak increase in the risk of a more aggressive tumor type with increasing smoking intensity in former smokers, but this association was absent in current smokers. This conflicting result may suggest that there is no strong relation between smoking intensity and bladder cancer aggressiveness. Analyses of prospective studies with longitudinal smoking assessment may provide a more definitive answer to the research question.